REKAYASA SALINITAS MEDIA PEMELIHARAAN SEBAGAI UPAYA DOMESTIKASI IKAN GIRU (Amphiprion ocellaris) YANG BERASAL DARI KEPULAUAN SIMEULUE - Sufal Diansyah; Munandar Munandar; Afrijal Afrijal (Universitas Teuku Umar, 2016)
Clownfish (Amphiprion ocellaris) is one reef fish that can be used as ornamental fish saltwater aquarium. The fish has high economic value because the color is attractive. However, this time facing the difficulty found the seeds found in nature as a result of uncontrolled harvesting, especially in the northwest district of Simeulue. The purpose of this study is a way of domestication of clownfish in a population that is almost extinct (endangered) of wild life (natural habitat) into the cultivation environment to determine the viability of a clownfish by administering salinity 32, 30, 28 and 26 ppt performed for 60 the aquariums in a container measuring 60 cm (long), 40 cm (wide) and 40 cm (high). The results showed that administration of different salinity did not significantly affect survival (p>0.05), while the absolute growth rate and feed conversion showed significant results (p<0.05), the value range of the absolute growth rate was ± 0.0014 to 0.00444 grams of feed conversion has a value range of ± 1,311- 5.190 grams.